(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The research was conducted to adapt the Perendale, Dorper, and Suffolk sheep and evaluate their productive and reproductive performances. Materials and Methods: Data from 82 pure exotic sheep were recorded within the period of 2016–2024. The considered traits were birth weight, live weight at 3 (BWT3), 6 (BWT6), 9 (BWT9), and 12 months (BWT12), adult weight (2–3 years), average daily weight gain at 0–3 (ADG0-3), 3–6 (ADG3–6), 6–9 (ADG6–9), and 9–12 (ADG9–12) months of age, wool production, age at first conception, gestation length, litter size, age at first lambing, lambing interval, and days open. The data were analyzed using R software version 4.4.2. Results: Breed had no significant effect on productive and reproductive traits except BWT3, ADG0- 3, wool production per sheep per shearing, and average lambing interval. The highest BWT3 (kg) and ADG0-3 (gm/day) were found in Dorper sheep, followed by Suffolk and Perendale, and the values were 23.15, 22.19, and 19.39 and 216.52, 210.86, and 173.12, respectively. In the case of wool production per sheep per shearing (kg), the highest production was found in Suffolk compared to Perendale and Dorper, respectively. The lowest lambing interval (days) was found in Dorper sheep, followed by Suffolk and Perendale, respectively. The average survivability rate of lambs and growing sheep was 96.34 and 98.73, respectively. Conclusion: The findings indicate that exotic sheep are well-adapted to our environment, and Dorper sheep may be utilized to produce meat-type crossbred sheep. J. Adv. Vet. Anim. Res., 12(4): 1250–1258, December 2025 http://doi.org/10.5455/javar.2025.l986